Cumplimiento del seguimiento de enfermería a pacientes con hipertensión arterial del Subcentro de Salud Tarqui de Puyo año 2013-2014 - Chacha Chacha, Isabel Cristina (2014)
The reason for the study is the fulfillment of monitoring nursing to patients with hypertension users subcentre Tarqui Canton Puyo Pastaza Province; The problem noted was the high demand for care of patients presenting with elevated pressures. The purpose of this research is to determine the level of compliance monitoring nursing to contribute to improving the quality of life while encouraging physical exercise as a complementary treatment of hypertension subcentre users. The research is experimental, transverse, literature, field and descriptive, quantitative and qualitative design type. For data collection, the survey for which a questionnaire was developed to assess nursing intervention for patients with hypertension applied the same had the following results of the investigation show that the level of compliance in monitoring patients with hypertension is low with a percentage of 62% and 22% indicates the median and 15% rated it as excellent. Which leads to the conclusion that monitoring nursing is not performing at an optimal level. A proposal for self-care with the dissemination of healthy lifestyles, exercise, music therapy and tai chi was developed. Educational activity was performed according to the manual. Educational brochure after completing the educational activity to licensed nursing coordinator was delivered. Keywords: Hypertension, Patient Monitoring, Compliance Complicate